2002
DOI: 10.1097/01.asn.0000027355.41663.14
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Biologic and Functional Analyses of Five New Aquaporin-2 Missense Mutations that Cause Recessive Nephrogenic Diabetes Insipidus

Abstract: Abstract. Mutations in the Aquaporin-2 gene, which encodes a renal water channel, have been shown to cause autosomal nephrogenic diabetes insipidus (NDI), a disease in which the kidney is unable to concentrate urine in response to vasopressin. Most AQP2 missense mutants in recessive NDI are retained in the endoplasmic reticulum (ER), but AQP2-T125M and AQP2-G175R were reported to be nonfunctional channels unimpaired in their routing to the plasma membrane. In five families, seven novel AQP2 gene mutations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 49 publications
11
96
0
Order By: Relevance
“…It is interesting that the total and plasma membrane expression as well as the Pf of AQP2-R254L and AQP2-S256A were similar, which indicated that the molecular cause for AQP2-R254L in dominant NDI indeed could be the lack of S256 phosphorylation. As shown for AQP2-S256A (5,20), functional AQP2 mutants in recessive NDI (13,22,23), a retained AQP2 mutant in dominant NDI (AQP2-E258K [7,22]), and also here for wt-AQP2 ( Figure 2), the conferred water permeability for AQP2-R25L was related directly to its expression level ( Figure 2C). …”
Section: Functional Analysis Of Aqp2-r254l In Oocytessupporting
confidence: 58%
See 2 more Smart Citations
“…It is interesting that the total and plasma membrane expression as well as the Pf of AQP2-R254L and AQP2-S256A were similar, which indicated that the molecular cause for AQP2-R254L in dominant NDI indeed could be the lack of S256 phosphorylation. As shown for AQP2-S256A (5,20), functional AQP2 mutants in recessive NDI (13,22,23), a retained AQP2 mutant in dominant NDI (AQP2-E258K [7,22]), and also here for wt-AQP2 ( Figure 2), the conferred water permeability for AQP2-R25L was related directly to its expression level ( Figure 2C). …”
Section: Functional Analysis Of Aqp2-r254l In Oocytessupporting
confidence: 58%
“…Selection of G418-resistant clones and immunocytochemistry of transfected MDCK cells were done as described (16). MDCK cell lines that stably expressed wt-AQP2 (wt-10), AQP2-S256A, or green fluorescent protein (GFP)-tagged AQP2 were as described (13,17,18).…”
Section: Mdck Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if the osmotic pressure in the colon increases via the administration of bisacodyl, as indicated in the above-mentioned mechanism, water transfer from the luminal side of the cells is decreased under the condition of decreased expression level of AQP3 in the colon. This occurs because the rate of water transfer via AQPs depends more on the expression level of AQPs on the cell surface than on the difference in the osmotic pressure between the inside and outside of the cells (21,36). Therefore, it is more appropriate to regard the mechanism of the laxative effect of bisacodyl as inhibited water absorption caused by a decrease in the expression of AQP3 in the colon than increased water secretion caused by an increase in the osmotic pressure in the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most mutations identified in the AQP2 gene in NDI are manifested as mis-routing errors rather than as structural defects that affect their ability in conducting water across the membrane. Some of these mutations, including L22V, L28P, A47V, V71M, T126M, A147T, V168M, P185A, R187C, E258K, and P262L have been characterized in Xenopus oocytes, yeast, and/or mammalian cells, and have been shown to have impaired folding, resulting in recognition by the endoplasmic reticulum (ER) quality control machinery, ubiquitination, and degradation by the 26S proteasome (Boccalandro et al, 2004;de Mattia et al, 2004;Deen et al, 1995;Kamsteeg et al, 2008;Kamsteeg et al, 2009;Levin et al, 2001;Marr et al, 2002;Mulders et al, 1997;Tamarappoo and Verkman, 1998). However, these AQP2 mutants are found to be intrinsically functional water channels when being characterized.…”
Section: Factors Involved In Aqp2 Endocytosis and Exocytosismentioning
confidence: 99%